Encountering God through human experience: the life and thought of Luigi Giussani (Memorandum: Memória e História em Psicologia, 2012)
This article gives an introduction to the life and thought of Luigi Giussani (1922-2005), a Catholic theologian who is the founder of the Communion and Liberation movement. Its focus is on Giussani’s proposal of the Christian life, not simply as a set of rules or a system of thought, but as an encounter with the person of Christ. As a consequence, experience is placed at the centre of faith because God himself experienced humanity in history. Since Giussani’s life was built alongside his theological articulation, the article then discusses the foundational concept of “religious sense”, briefly highlighting its developments in education and psychology, and concludes with the correspondent answer of revelation in Christianity.